PENGARUH TINGKAT LITERASI KEUANGAN SYARIAH TERHADAP MINAT BERINVESTASI DI GALERI INVESTASI SYARIAH (STUDI KASUS MAHASISWA FAKULTAS EKONOMI DAN BISNIS ISLAM UNIVERSITAS ISLAM NEGERI SULTHAN THAHA SAIFUDDIN JAMBI ANGKATAN 2020) - Ega Larasati; Suhar; Nurrahma Sari Putri (Program Studi Ekonomi Syariah Sekolah Tinggi Agama Islam Negeri Mandailing Natal, 2024)
Syaria financial literacy refers to the definition of financial literacy of the Financial Services Authority, which is a consumer of sharia financial products and services with the aim of knowing and understanding sharia financial service institutions and managing sharia finance so as to increase benefits. The aim of this research is to determine the influence of sharia financial literacy on interest in investing in the sharia investment gallery among students at the Faculty of Economics and Islamic Business, UIN STS Jambi Class of 2020. This research method is descriptive quantitative research. The population in this study, namely students from the Faculty of Economics and Business, was 509 students. The sample was 84 students with a sampling technique using probability sampling. The research instrument uses observation and questionnaires, and documentation. The results of this research show that sharia financial literacy has an influence on interest in investing in the Sharia Investment Gallery with a significance value of 0.000<0.05. If sharia financial literacy increases, interest in investing will also increase. Based on the coefficient of determination, it indicates that sharia financial literacy factors can influence investment interest by 66.3%. The simple linear regression equation formed is: Y= 6,277 + 0,408 X.